PERTANGGUNGJAWABAN SUAMI TERHADAP HUTANG ISTRI MENURUT HUKUM ISLAM SEBAGAI UPAYA MEWUJUDKAN KEHARMONISAN RUMAH TANGGA (Studi Kasus Di Desa GondangWetan Kecamatan Jatikalen Kabupaten Nganjuk) - Zahrotul Ulfa (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The husband's responsibility for his wife's debts according to Islamic law in Gondang Wetan Village, Jatikalen District, Nganjuk Regency can be started by highlighting the importance of understanding and applying Islamic law in everyday life, including in the context of the husband's responsibility for family debts. This research is to understand the concept of debt settlement wife according to Islamic law. This research is field research. The method used in this research is a qualitative method with an empirical juridical approach. The results of this research show that people have different views about the husband's responsibility for his wife's debts, some people in Gondang Wetan Village agree that the wife's debts are the husband's responsibility if the wife is married, so everything related to the wife is the husband's responsibility, and If the wife is able to pay the debt then it is permissible. In Islamic law, the person who has the obligation to pay and settle debts is the individual and joint debts in the family, it is the husband, because the husband is the head of the household and the leader of the family. Meanwhile, the settlement of default debts is borne by each party unless agreed otherwise before the marriage (pre-nuptial agreement)